Designing the Flipped Classroom Strategy in Teaching Grammar - Johari, Johari; Ahmad, Arimuliani; Salsabila, Intan Syazwina (Journal of English Language and Education, 2024)
This study provides a simple design of a flipped learning instructional model to teach Basic English grammar at a Private University in Riau. Bloom's taxonomy of educational objectives was utilized as an underpinning to develop a top-down flipped learning model. To support student learning outside of the classroom, Google Classroom, an LMS, was used as a platform to disseminate pre-class video lectures. Moreover, this study employed a design-based research (DBR) approach for instructional technology, which provided several phases, namely; planning, designing, formative evaluation, revising, re-designing, and summative evaluation. Researchers suggest watching, summarizing, and taking notes as the three main tasks that can be done outside the classroom; while discussions and presentations are the main activities that occur in class. The findings of this study have consequences for authorities who should take into account flipped classrooms as the current method of instruction for providing grammar and other disciplines in any higher education institution in Indonesia.